Understanding the role of emotion in ethical consumption: a tourism context - Malone, Sheila (2012)
This thesis investigates the role of emotion in an ethical consumption context. It responds to a call by many researchers for greater knowledge of ethical issues in the field of marketing and consumer behaviour. This interest has emerged from a growth in ethical consumption practices despite hard economic times. The limitations of the renowned intention-behaviour gap highlight that such practices cannot be wholly explained by rational processes alone. However, little attention has been afforded to the impact of non-rational factors such as emotion. By examining the concept of emotion, this study addresses previously ignored consumption phenomena identified in the experiential perspective of consumer behaviour. More specifically, this thesis concentrates on tourism as an experiential consumption encounter and as a prototypical moral platform on which ethical practices has resulted in a plethora of alternative tourism offerings. This study employs semi-structured interviews with self-defined ethical tourists using an Interpretative Phenomenological Analysis (IPA) approach. This approach helped uncover participants' subjective experiences, their meaning and how they make sense of these encounters. The findings of this thesis demonstrate the difficulties experienced by the participants in communicating emotional experiences. As a result, they tended to use the senses to describe these encounters, thereby reflecting deeply engaging and emotional consumption experiences. The pivotal role emotion plays in the participants' ethical decision making is evident as it helps reaffirm an ethical sense of self, thereby influencing future ethical behaviours. Within the consumption experience, emotion appeared as a source of hedonic value often expressed through escape experiences and its concomitant feelings of freedom, through a sense of mutual benefit and in the challenge and achievement bestowed in the experience itself. Furthermore, the relationship between positive and negative emotions is evident highlighting the transformational effect of positive emotions and the influential impact of negative emotions on ethical consumption choices. The main contributions of this study are threefold. First, it contributes to the ethical literature by demonstrating ethical consumption to be a hedonic experience. It highlights emotion's key function in motivating, influencing, evaluating and engaging the participants with their consumption experiences. In particular, it contributes to the literature on ethical tourism as it highlights that the participants' desire to engage in ethical tourism is not only motivated by self-reflection based on their ethical beliefs and values, but also because of how these experiences make them feel. These feelings stem from an intrinsic enjoyment bestowed in choosing an ethical alternative and in the experience itself. Consequently, ethical tourism is regarded as a superior quality experience and a more meaningful consumption encounter. Second, this thesis contributes to the experiential perspective of consumer behaviour, by providing a greater understanding of the concept of emotion in an ethical consumption context. It identifies the central role of emotion prior to, during, and after decision-making in an ethical context. In addition, it demonstrates the motivational and influential role positive emotion has in promoting ethical behaviour, and the reinforcing role negative emotion has in discouraging unethical behaviour. Third, the thesis highlights the significance of pride as a consumption emotion, due to its impact on both a personal and an emotional level, and its ability to influence the individual's ethical decision-making processes. Finally, as a research context, the practical implications of this thesis are evident in their ability to influence marketing strategies employed in the tourism industry and their role in inform policy-makers is illustrated. Implications for future research are also considered.